Die aktuelle Kritik an der makroökonomischen Geldtheorie - Georg Quaas (Wirtschaftsdienst, 2017)
Eine universelle Übereinkunft darüber, was Geld eigentlich ist, gibt es nicht. Geld wird in einem Prozess geschöpft, an dem die Zentralbank, Geschäftsbanken und Haushalte, der Staat und Unternehmen beteiligt sind. Deren Rolle wurde im Monatsbericht der Deutschen Bundesbank vom April 2017 erläutert. Damit wurde eine Diskussion vor allem zu zwei Fragestellungen ausgelöst: Benötigen Banken Sparer, um Kredite zu vergeben, oder schöpfen sie Geld einfach selbst? Welche Beziehung besteht zwischen Geldbasis und Geldmenge? – – There is no universal agreement on what money actually is. Money is created and used by the modern bank system, which can be split into the central bank, the commercial banks and the remaining sector of households, companies and states. The article focuses on bank deposits, which are created by commercial banks themselves. Bank deposits count as money in a modern economy such as Germany, where the bulk of money held by the public is in the form of deposits with banks. The other part is currency - bank notes and coins. Not accessible to the public (with some exceptions) are central bank reserves held by commercial banks with the central bank. There are two main problems which are currently being discussed by the Deutsche Bundesbank and by some more or less academic authors. First, what kind of relationship exists between base money (currency and reserves) and bank deposits? This relationship plays a crucial role in controlling and steering inflation and investment. Second, are banks lending the savings of their customers to other customers? This relationship is a cornerstone of the money multiplier theory. The answers to these two questions are not as trivial as they seem to be. Textbooks are of no help because they are the targets of the criticism made by central bank authors.
Keywords: E51; E13; B59; 330